Perilaku Bisnis Muslimah : Muslimah Berkeluarga Anggota IWAPI di Kota Surabaya - Permatasari, Sesha Ayu; Nafik HR, Muhammad (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The purpose of this research is to know whether the business behavior of a Muslim family of IWAPI members in Surabaya in accordance with the teachings of Islam. This study used a qualitative approach explanatory case studies. Data collection techniques using in-depth interviews, interviews, participant observation and documentation.In this study, the behavior of the Muslim business in terms of aspects of motivation, commitment to family, barriers experienced, responsibilities and activities as well as adopting a business strategy which includes four properties of the Prophet namely: Siddiq, Trustworthy, Fatonah, Sermons. Results of this study are doing business is not forbidden in Islam as long as it does not ignore the views of the main task of a Muslim as a housewife. Business motivation ofhousewives is gain a flexible time management so as to enable a balance between the obligations of housewives and business. Thus a Muslim is able to prove that a Muslim could succeed as a wife, IWAPI members and businesswomen.